The Radiograph of Lung Lobationof the Sunda Porcupine (Hystrix javanica)(RADIOGRAFI LOBUS PARU-PARULANDAK JAWA (HYSTRIX JAVANICA)) - Suparmin, Yuliani; Gunanti, Gunanti; Noviana, Deni; Agungpriyono, Srihadi (Jurnal Veteriner, 2020)
Sunda porcupine (Hystrix javanica) is one of the endemic porcupine species in Indonesia. The importance of wild species preservation brings with it the requirement for more basic aspects of anatomy. The knowledge of the normal radiological anatomy of the lung is of crucial importance for the making of a correct diagnosis of lung diseases. This study aimed to provide information about the radiographic anatomy in the lung lobation of sunda porcupine. This study was an explorative study using four sunda porcupines. Thoracic radiograph was retrieved using conventional and digital X-ray machine. Standard projections for thoracic radiography used lateral and ventrodorsal projection. The evaluation result of thorax radiogram showed that interlobar fissures separate the different lobes. The porcupine right lungs consist of four lobes, i.e. cranial lobe (cranial and caudal segment), middle lobe, caudal lobe, and accessory lobe, while left lung consisted of only two lobes, i.e. cranial lobe (cranial and caudal segment) and caudal lobe.